Optimizing community-based artisanal fisheries approach to improve coastal resilience and community livelihoods - Teguh Prawira Wahyu; Widyasari Vincentia; Widyanto Adi (BIO Web of Conferences)
Coastal ecosystems and the livelihoods of communities dependent on them face growing threats from overfishing, habitat loss, and climate change. Artisanal fisheries, community-driven fishing practices, offer a potential solution for promoting both environmental conservation and economic resilience. This paper explores the optimization of community-based (CB) artisanal fisheries management as a means to enhance coastal resilience and improve livelihoods. By integrating traditional ecological knowledge with modern sustainable fishing techniques, communities can develop adaptive strategies to mitigate the impacts of environmental changes while ensuring the sustainable use of marine resources. The approach focuses on community-based participatory governance, where communities and stakeholders at the grassroots level are actively involved in decision-making processes, leading to more equitable resource distribution and a stronger sense of ownership over the marine resources around them. Furthermore, locally relevant innovations, such as local marine protected areas and seasonal fishing bans, have been shown to increase fish stocks, enhance biodiversity, and stabilize incomes. Case studies from coastal areas under the Wallacea II Partnership Program highlight this approach's positive outcomes, demonstrating its potential as a replicable model for balancing conservation and socio-economic development. The paper concludes with recommendations for replicable community-based small-scale fisheries governance approaches to support broader coastal resilience strategies.